Life is a raffle: community social imaginary in the presence of covid-19 - Mora-Rosales, José Clemente (2022)
The purpose of this essay was to reflect on the possibility of being infected with COVID-19, by transgressing the rules of self-care, which invites us to do so from the metaphorical of the phrase "life is a tombola"; to focus on the impact that came from hearing "it's not going to happen to me", while touring the "garden city" of Venezuela, I perceived an aspect of the community imaginary, regarding the meaning they gave to the risk of contagion, which has altered the daily life of the community. It is a set of diverse voices and their shared narratives, to which I applied the hermeneutics of active listening, where key categories of the community social imaginary emerge, because they are the protagonists: the family, the people in the street, expressing the urban thought about the chance of contagion, about the Christmas festivities.